DESIGN ASSEMBLER BASED ON LEX AND YACC - Melhum, Amera; Mahmood, Suzan (Iraqi Journal of Science, 2024)
LEX and YACC are very useful tools for constructing the assemblers; they generatefunctions that perform standard operations of a lexical analysis and parsing withoutany effecting on the organization processes for semantic analysis, machine codegeneration and listing source of compilation. In this work, the cross assembler wasdesigned using some compiler development tools like LEX and YACC having theability to implement the lexical analyzer and parser, for generating the syntax andparsing modules in a short period of time. These activates are expressed in form ofactions, the bigger number of lexical and grammar rules are used by these actions ina simpler way.